Anglophone Africa in the Olympic Movement : The Confirmation of a British Wager? (1948-1962) - (:unkn) unknown (My University, 2011)
In July 2010 I discovered the National Archives (Kew, London) while working on a dual project: my doctoral thesis, and a grant awarded by the Olympic Studies Centre in Lausanne, Switzerland. My goal was to conduct a comparative historical analysis of the administrative and political colonial situations of the United Kingdom and France. I wanted to understand their influence on the integration of the former British and French colonies into the Olympic movement between the end of the Second World War (1945) and the hosting of the Olympic Games in London (1948) on the one hand, and colonial independence in Africa in the 1960s on the other, reflected at the IOC by the creation of the Committee for International Olympic Aid (CIOA) to help the new countries in the Third World.
Keywords: African Research